Examine the Role of Agriculture to Mitigate the Co2 Emission in Bangladesh - Rahman, Md Hasanur; Majumder , Shapan Chandra; Debbarman, Shantanu (Asian Journal of Agriculture and Rural Development, 2020)
The current study analyzed the optimum solution to mitigate CO2 emission in Bangladesh. The significant factor of this study is agricultural productions and activities in Bangladesh are the superior carbon absorber. To estimate the effective result and findings this perusal conducts the Generalized Method of Movement with considering agricultural productions as a key variable to mitigate the CO2 emission. The econometric result finds that agricultural production reduces carbon emission in selected models. An increase the agricultural activities and green harvesting significantly reduce CO2 emission. Whatever, the empirical result also states that increasing agricultural production is not only a productive way to mitigate CO2, also, that CO2 could be mitigated to invest in agriculture, provide initiative or subsidies in the agriculture sector. The current study provides a substantial way to mitigate carbon dioxide without any harms of economic growth.